The Islamic criminal laws: hudood, qisas and ta'zir laws - Jusoh, Hamid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2004)
What is the position of Islamic Law in Muslims states, particularly dealing with Hudud and Qisas punishment? Is it really imperative for the authority of Muslims states to implement it? Some peole say that Islamic criminal law in such form irrelevant since the reality of life is now different. Is it true? What is meant by reality? Do they really understand what they say? Sometimes they do not really understand. In this regard, the experience in Pakistan may be reffered to. The role of its Courts in upholding justice based on Islamic principles needs to be understood properly. As a result of that role, the laws in pakistan have been amended as parly contained in this book.